Minority Right to Attend Religious Education in Indonesia - Raihani Raihani (Al-Jami'ah: Journal of Islamic Studies, 2015)
In 2003, Indonesian government issued a new education law in which one of the articles (Article 12) states that student has the right to access religion class in school in accordance with his or her religion by teachers who share the faith. This particular article has a legal ramification that school --state and private-- by law must provide corresponding Religion Classes (RC) for each religious group of students in order to fulfill their very human basic right to access to and observe their religious and cultural teaching and practices. This paper presents findings of four different school case studies on the problem of access to RC by religious minority in schools in Indonesia. Minority in this paper refers to religious groups that are either numeric minority or subordinate majority at the micro school level, not in the macro national population. This paper argues that numeric minority in any context (micro or macro) is vulnerable to discrimination by the dominating majority when the law of social relations is not fairly implemented. The findings suggest that the right of religious minority groups in three of the four schools to access proper RC is stifled, particularly to access equal learning facilities. Numeric religious minority groups in these schools suffer from powerlessness. One case, however, demonstrates that the positional power of minority group reverses this logic of minority-powerlessness and puts the religious majority students in a subordinate position.[Tahun 2003, pemerintah Indonesia mengeluarkan Undang-Undang Pendidikan yang pada pasal 12 menyatakan bahwa siswa mempunyai hak terhadap pelajaran agama di sekolah dengan guru yang mengajar sesuai dengan agamanya. Pasal ini mempunyai konsekuensi bahwa sekolah, baik swasta atau pun negeri, harus menyediakan kelas agama untuk setiap kelompok siswa untuk mendapatkan hak dasarnya guna melaksanakan agama dan ajarannya. Artikel ini menampilkan hasil penelitian dari empat sekolah dengan studi kasus pada persoalan kelas agama bagi kelompok minoritas. Istilah minoritas di sini merujuk pada kelompok agama yang sedikit jumlahnya atau kelompok kecil pada sekolah, bukan pada level nasional. Tulisan ini menegaskan bahwa minoritas pada konteks mikro atau makro sangat rentan terhadap perlakuan diskriminasi oleh kelompok mayoritas ketika hukum social tidak sepenuhnya dijalankan. Penemuan ini menegaskan bahwa hak keagamaan minoritas dalam tiga dari empat sekolah terganggu, terutama yang terkait dengan hak fasilitas belajar. Beberapa kelompok minoritas pada sekolah tersebut tak berdaya. Namun, satu kasus menunjukkan bahwa kondisi minoritas berbalik, justru  kelompok mayoritas yang menjadi subordinasi.]